TINJAUAN MANAJEMEN PENGELOLAAN DAN PENGEMBANGAN TEMPAT REKREASI DI DANAU TALANG - Putra, Rizki Pratama; Andri Gemaini; Nugroho Susanto; Ahmad Chaeroni (Jurnal IKEOR, 2023)
problem in this research is that judging from the management of the Talang lake recreation area, until now there is still a lack of management so that it has an impact on the slow progress of recreational sports tourism. This research is included in qualitative research. That is a form of research procedure that produces descriptive data in the form of speech or writing and behavior that can be observed from something. With a qualitative approach, this research is expected to reveal comprehensive facts about the development of tourism management and the development of recreational sports at the Talang Lake tourist attraction. Based on the research findings above, the Talang Lake recreation area has management that has not gone well because there are still several conflicts or problems that hinder development in the management of the Talang Lake recreation area, one of which is the Talang Lake area which still has the status of a protected forest area which hinders development. and infrastructure development.